Unusual presentations of Comamonas kerstersii infection. (September 2017) - Almuzara, M.; Barberis, C.; Veiga, F.; Bakai, R.; Cittadini, R.; Vera Ocampo, C.; Alonso Serena, M.; Cohen, E.; Ramirez, M.S.; Famiglietti, A.; Stecher, D.; del Castillo, M.; et al.
Abstract: The association of Comamonas kerstersii with peritonitis resulting from the presence of perforated appendix has previously been described by our research team. In the present study, we describe the isolation of this microorganism from two forms of unusual presentations of C. kerstersii infection not previously described in the literature: localized intra-abdominal infection (psoas abscess) and pelvic peritonitis.